Сучасний стан та перспективи розвитку фестивального туризму в Україні - Деркач, Аліна Сергіївна; Derkach, A. (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Роботу присвячено дослідженню сучасного стану та перспективам розвитку фестивального туризму в Україні. Вивчено сутність та визначення фестивального туризму. Розглянуто класифікацію видів фестивального туризму. Досліджено закордонний досвід розвитку фестивального туризму. Оцінити ресурсне забезпечення фестивального туризму в країні. Проаналізовано та виявлено проблеми розвитку фестивального туризму. Визначено перспективи розвитку фестивального туризму в Украйні.

This paper is devoted to the study of the current state and future prospects for the development of festival tourism in Ukraine. The concept and definitions of festival tourism are explored. Various types of festival tourism are classified and analyzed. International experience in the development of festival tourism is examined. The resource base for festival tourism in Ukraine is assessed. The study identifies key problems hindering the development of this tourism segment and outlines strategic directions for its further advancement.
The current state and prospects for the development of festival tourism in Ukraine
Керівник: Панова Ірина Олексіївна, кандидат економічних наук, доцент кафедри світової політики, дипломатії та туристичного бізнесу
Keywords: SOCIAL SCIENCES; фестивальний туризм; туристична інфраструктура; культурні події; регіональний розвиток; подієвий туризм; festival tourism; tourism infrastructure; cultural events; regional development; event tourism